LA ENSEÑANZA DE LA FÍSICA A TRAVÉS DE MODULOS EXPERIMENTALES - RONALD AVENDAÑO; FABIO OMAR ARCOS; OLGA CASTIBLANCO; WILSON LANCHEROS (Universidad Distrital Francisco José de Caldas, 2012)
This proposal for teaching and learning physics was developed in two private educational institutions in Bogotá, Colombia. With students between 13 and 18 years old. We research different educational possibilities throughout experimental work in the classroom. We planed, applied and analyzed five modules for lab, eachone with small goals to achieve an overall objective. The process was designed according to the proper characteristics about physics topics and assembly dificulties. The modules were about; mechanics, electricity, thermodynamics, fluid mechanics and waves, by means of 5 modules that were titled: Tractor mechanic, Heat engine, Wind tunnel, Van Der Graff generator and Doppler effect. In general they consist on; design, construction, operation and explanation. We observed active participation of students on their learning process, interdisciplinary work, and reflections about science and technology impact over the society.